2019
DOI: 10.1038/s41598-019-49126-9
|View full text |Cite
|
Sign up to set email alerts
|

Consumption of benthic cyanobacterial mats on a Caribbean coral reef

Abstract: Herbivory is an important process in the general structuring of coral reef benthic communities. However, evidence of its ability to control coral reef benthic cyanobacterial mats, which have recently proliferated on reefs worldwide, remains ambivalent. Here, we report that the French Angelfish ( Pomacanthus paru ), Striped Parrotfish ( Scarus iseri ), Rock Beauty ( Holacanthus tricolor ), Ocean Surgeonfish ( Acanthurus bahianus … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
44
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 29 publications
(48 citation statements)
references
References 55 publications
2
44
2
Order By: Relevance
“…As such we could have expected some species to opportunistically make use of the new dominant resource. These results also contrast to those of Cissell et al 32 who identified several species to be consuming mats in the Caribbean. Reasons for these differences could include the presence of different herbivorous fish species, because of difficulties in visually determining what fish are feeding on, or differences in mat composition and chemistry.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…As such we could have expected some species to opportunistically make use of the new dominant resource. These results also contrast to those of Cissell et al 32 who identified several species to be consuming mats in the Caribbean. Reasons for these differences could include the presence of different herbivorous fish species, because of difficulties in visually determining what fish are feeding on, or differences in mat composition and chemistry.…”
Section: Discussioncontrasting
confidence: 99%
“…It’s likely that differences in the metabolites produced by different BCMs, along with variation in tolerance to the metabolites by different fish species, can in part explain discrepancies in observations of grazing on BCMs between this study and others (e.g. Cissell et al 32 ).…”
Section: Discussioncontrasting
confidence: 52%
See 1 more Smart Citation
“…Previous studies have shown that larger herbivorous species such as acanthurids are the main contributors to macroalgal control (Ceccarelli et al 2006;Rasher et al 2013). Although cyanobacterial top-down control is less understood, partly due to the fact cyanobacteria have been considered largely unpalatable to many broad consumers, recent studies suggest an important role of top-down control on cyanobacterial mats (Capper et al 2016;Cissell et al 2019). Previous studies have reported cyanobacteria as an important ingredient in several damselfish species diets (Lassuy 1984;Feitosa et al 2012).…”
Section: Discussionmentioning
confidence: 99%
“…vulpinus may need to supplement its diet with other food sources that, while less preferred, produce less toxin. For instance, dense, mat-forming species of cyanobacteria (e.g., genus Lyngbya) are expected to produce more toxins than their sparser counterparts (Cissell et al, 2019). Consequently, short patch residence times and wide movements for Si.…”
Section: Discussionmentioning
confidence: 99%